Exploring Excellence: A Literature Review on Service Quality in the Hospitality Industry - Coronel, Paul Justine Panganiban (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Service quality, defined as customers’ perceptions of service com-pared to their expectations, is critical in the hospitality industry (Vidyanata, 2022). Consistently meeting the diverse expectations of a broad customer base remains a significant challenge for ser-vice providers (Pomegbe et al., 2019). This review examines 25 empirical studies, summarizing their key findings and approaches to consolidate insights into service quality. It highlights fundamen-tal concepts, theories, and practical applications while identifying research gaps and inconsistencies. Key themes include the impact of service quality on customer satisfaction, loyalty, reputation, employee satisfaction, organizational success, and competitive advantage. Influencing factors identified include customer satis-faction, organizational processes, and technology. The study also offers strategies for improving service quality, providing actiona-ble insights for the hospitality industry.